DISCOVERY LEARNING DENGAN MEDIA ULAR TANGGA NUMERASI : EKSPERIMENTASI PADA SISWA SD - Cahyani, Arum; Yustitia, Via; Hadi, Susilo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Numeracy skills include understanding and applying number concepts in everyday life. Low student interest and understanding in learning mathematics and lack of interaction in the learning process. This research analyzes Discovery Learning with snakes and ladders media as an interactive tool This study aims to determine whether there is an effect of recovery learning assisted by snakes and ladders media on the numeracy skills of fourth grade students of SDN Gamping 01. Through Discovery Learning assisted by snakes and ladders media, it is expected to increase understanding and numeracy skills that are more contextual. This research used a quantitative approach with a one shot case study experimental design. The population in this study were all fourth grade students of SDN Gamping 01. This sample was taken using random sampling technique. The sample of this study involved 30 fourth grade students. Data collection techniques used tests and documentation. Research instruments in the form of 8 numeracy test items in the form of descriptions. Data analysis techniques include normality test, homogeneity test, and t-test to determine the effectiveness of the learning method used. The results of data analysis using SPSS 16 showed that the use of Discovery Learning method assisted by snakes and ladders media had an effect on the numeracy skills of fourth grade students of SDN Gamping 01.The use of Discovery Learning assisted by snakes and ladders media proved effective in improving students' numeracy skills. The results of this study can be a reference for educators as an innovative learning model and media in improving numeracy skills at the elementary school level.